O dado linguístico e os fatores histórico-geográficos: o que mostra o léxico dos jogos e diversões infantis acerca do processo de povoamento do Maranhão - CASTRO, Gabriel Pereira (2022)
This is a study that interrelates data of a geolinguistic nature and historical data, concerning the population process of Maranhão, from the perspective of lexical variation. The State, as Trovão (2008) points out, comes from two distinct fronts of occupation, with their own characteristics, which generated a society with distinct sociocultural patterns between north and south. Considering this reality, this work is based on Dialectology and Pluridimensional Geolinguistics and also on Lexicology and aims to investigate, based on data from the Projeto Atlas Linguístico do Maranhão – ALiMA, if the diatopic distribution of lexical variants, in the semantic area of games and children's amusements, reflects the process of populating Maranhão and if it is possible to draw isolexic lines that contribute to better explain the present based on the past, on historical fact. The central hypothesis of the dissertation starts from the idea that the municipalities that are located in the portion of Maranhão covered by the Settlement Front of Sertão or Pastoral, coming from the northeastern interior, reveal, in the lexicon, a proximity to Piauí and Bahia, thus distancing themselves from the municipalities of the other portion whose settlement process took place via the Coastal Front. For the examination of this hypothesis, the 16 questions of the area under study, questions 168 to 183 of the Semantic- Lexical Questionnaire – SLQ, adopted by ALiMA, were selected, and the answers to them given by the 68 informants of the ALiMA Project. The research locus comprises the 16 municipalities that make up the network of ALiMA inquiry points; these points cover all the mesoregions of the State. The results obtained point to lexical differences in the context of children's games and games that can lead to the conclusion that these differences show reflections of the State occupation process, a result of the different settlement fronts. The names obtained for the concepts present in questions 168, 176 and 183 illustrate this fact. Some items, however, such as the kite and the shuttlecock, are used in a uniform way, without conditioning the population processes of Maranhão. The observation of lexical variation in the diatopia axis also indicated evidence of the intermediate position that Maranhão, and more particularly its capital, São Luís, occupies between the North regions, considering that it is linked to the colonization of the Amazon, as stated by Nascentes (1953), and Northeast. As a final product, there are 17 lexical letters, 16 diatopic and one isolexic, which make explicit the linguistic diversity.